2019
DOI: 10.1186/s13075-019-1954-3
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis synovial fibroblasts promote TREM-1 expression in monocytes via COX-2/PGE2 pathway

Abstract: Background Triggering receptor expressed on myeloid cells-1 (TREM-1) is inducible on monocyte/macrophages and neutrophils and amplifies the inflammatory response. The aim of this study was to determine whether rheumatoid arthritis synovial fibroblasts (RASF) promote the expression of TREM-1 in monocytes and its potential regulatory mechanism. Methods Synovial fluid and paired peripheral blood from rheumatoid arthritis (RA) patients were analyzed using flow cytometry. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 55 publications
(69 reference statements)
2
21
0
Order By: Relevance
“…In this study, the expression of COX-2 in the study group was significantly higher than that in the control group. A large number of studies have shown that COX-2 is highly expressed in patients with RA ( 20 , 21 ), which is consistent with our findings. Therefore, COX-2 inhibitors have been widely used in clinical practice, especially in the treatment of RA ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the expression of COX-2 in the study group was significantly higher than that in the control group. A large number of studies have shown that COX-2 is highly expressed in patients with RA ( 20 , 21 ), which is consistent with our findings. Therefore, COX-2 inhibitors have been widely used in clinical practice, especially in the treatment of RA ( 22 , 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…MMPs expressed by synovial cells and chondrocytes in RA are thought to play a pivotal role in cartilage destruction (Takaishi, Kimura, Dalal, Okada, & D'Armiento, 2008). In addition, these cytokines appear to play a critical role in up-regulation of cyclooxygenase-2 (COX-2) expression and subsequent production of prostaglandin E2 (PGE2) resulting in cartilage degradation and inflammation (Mateen et al, 2016;Peng et al, 2019 1β-induced prostaglandins E2 and MMPs, thereby acting as potential compounds to ameliorate the clinical outcomes in arthirits (Li et al, 2007;Meyer, Ueberham, & Gebhardt, 2004). Dehghani et al indicated that 1,000 mg garlic supplementation for 12 weeks might reduce pain severity in women with knee osteoarthritis (Dehghani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Frommer et al showed that FFA contribute to the pathogenesis and damage in RA, OA, and PsA, since stimulation of FLS with oleic, palmitic, and linoleic acid induced the secretion of proinflammatory cytokine IL-6, the chemokines IL-8 and MCP-1, as well as the matrix metalloproteinases pro-MMP1 and MMP3 [185]. Arachidonic acid (ARA) is the precursor of classically described prostaglandins (PGE2), which are known to be involved in inflammation in general, but also in arthritis [186,187].…”
Section: Pro-inflammatory Metabolitesmentioning
confidence: 99%